2018
DOI: 10.1021/acsami.8b11062
|View full text |Cite
|
Sign up to set email alerts
|

Low Interface Energies Tune the Electrochemical Reversibility of Tin Oxide Composite Nanoframes as Lithium-Ion Battery Anodes

Abstract: The conversion reaction of lithia can push up the capacity limit of tin oxide-based anodes. However, the poor reversibility limits the practical applications of lithia in lithium-ion batteries. The latest reports indicate that the reversibility of lithia has been appropriately promoted by compositing tin oxide with transition metals. The underlying mechanism is not revealed. To design better anodes, we studied the nanostructured metal/Li2O interfaces through atomic-scale modeling and proposed a porous nanofram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 62 publications
(91 reference statements)
2
11
0
Order By: Relevance
“…[28] Two distinct Mn 2p signals at 653.6 and 641.8 eV can be assigned to Mn2p 1/2 and Mn2p 3/2 , respectively ( Figure 4e). [12,37] Moreover, the aforementioned peaks and their corresponding satellite peaks at 654.7 and 643.2 eV are well consistent with those of MnO in the literatures (Figure 4e). [8] XPS characterization of NC@MnO HHSs confirms that the C 1s spectrum can well fit to six peaks at 284.3, 284.8, 285.5, 286.5, 288.0 and 289.3 eV, which correspond to C=C, CÀ C, CÀ N, CÀ OH, C=O and OÀ C=O components, respectively ( Figure 4f).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…[28] Two distinct Mn 2p signals at 653.6 and 641.8 eV can be assigned to Mn2p 1/2 and Mn2p 3/2 , respectively ( Figure 4e). [12,37] Moreover, the aforementioned peaks and their corresponding satellite peaks at 654.7 and 643.2 eV are well consistent with those of MnO in the literatures (Figure 4e). [8] XPS characterization of NC@MnO HHSs confirms that the C 1s spectrum can well fit to six peaks at 284.3, 284.8, 285.5, 286.5, 288.0 and 289.3 eV, which correspond to C=C, CÀ C, CÀ N, CÀ OH, C=O and OÀ C=O components, respectively ( Figure 4f).…”
Section: Resultssupporting
confidence: 90%
“…The N‐doping of carbon hollow spheres can form the defect and offer more active sites for the fast Li + absorption and diffusion, resulting in high electrical conductivity and outstanding rate capability . Two distinct Mn 2p signals at 653.6 and 641.8 eV can be assigned to Mn2p 1/2 and Mn2p 3/2 , respectively (Figure e) . Moreover, the aforementioned peaks and their corresponding satellite peaks at 654.7 and 643.2 eV are well consistent with those of MnO in the literatures (Figure e) .…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The presence of metallic Fe with uniform distribution provides additional fast pathway for electron transport, which could enhance the electron transfer kinetics . Furthermore, previous studies have demonstrated that the coarsening of Sn nanograins could inevitably take place in the mixture of Sn/Na 2 S during the desodiation process, which reduces the reversibility of the sodiation/desodiation reaction for SnS 2 . In this work, the uniformly distributed nanosized Fe grains could act as barriers and effectively hamper the migration of Sn nanograins, thus preventing the coarsening of Sn phase.…”
Section: Resultsmentioning
confidence: 87%